Pengaruh struktur modal dan profitabilitas terhadap nilai perusahaan pada perusahaan semen yang terdaftar di Bursa Efek Indonesia - Tarsono, Ono; Setianingsih, Ika (Jurnal Manajemen, 2024)
This research aims to determine the effect of capital structure and profitability on company value in cement companies listed on the Indonesia Stock Exchange (BEI) in 2016-2021. The population of this research is cement companies listed on the IDX. Sample selection was carried out using saturated sampling techniques. In this research, there were 6 (six) cement companies which were all used as samples. This research uses a quantitative approach using secondary data. The data analysis technique uses multiple regression analysis using SPSS v25 software. Based on the research conducted, it can be concluded that Capital Strutkur, which is proxied by the Long Term Debt to Equity Ratio (LTDER), has no effect on Price to Book Value (PBV). Profitability as proxied by Return on Assets (ROA) has a positive and significant effect on Price to Book Value (PBV) and Return on Investment (ROI) has a negative and significant effect on Price to Book Value (PBV).